A Case of Severe Aeromonas Bacteremia with Necrotizing Fasciitis of Lower Limb and Fournier's Gangrene in a Post-Allogenic Unrelated Hematopoietic Stem Cell Transplant Recipient - Das, Bikram; Ghafur, Abdul; S., Jeyasankar; Easow, Jose M. (South Asian Journal of Cancer, 2022)
Background Aeromonas is a water-dwelling Gram-negative bacillus primarily associated with gastrointestinal tract diseases. Aeromonas sobria causing gastroenteritis has been reported in India. In immunocompromised host, Aeromonas sobria can also present with severe necrotizing skin and soft tissue infection with a high mortality rate. We report a case of Aeromonas sobria sepsis with skin and soft tissue infection in the background of immunosuppression.Case Presentation Fifty-year-old male who underwent an unrelated donor peripheral stem cell transplant for relapsed pre-B acute lymphoblastic leukemia in complete clinical remission on graft versus host disease prophylaxis, post-white blood cell engraftment presented with acute onset lethargy, lower limb pain without fever, or any skin changes initially. He rapidly worsened clinically over few days and developed sepsis, multiorgan dysfunction with the appearance of erythema and blister over the lower limb, and Fournier's gangrene of scrotum. He was found to have Aeromonas sobria bacteremia with isolated resistance to carbapenems while sensitive to all other classes of antibiotics. Despite appropriate antibiotic therapy and supportive measures, he succumbed to death for this invasive bacterial disease.Conclusion Aeromonas should be considered a cause of sepsis in immunosuppressed hosts, especially those with hematological malignancy presenting with necrotizing skin and soft tissue infection. Considering the virulence of this pathogen, despite the very susceptible antibiogram, such patients must be managed aggressively. Early recognition of the disease with a combination of medical and surgical management might help to improve the outcome.
Keywords: Aeromonas sobria; Fournier's gangrene; hematopoietic transplant infection; HSCT; necrotizing fasciitis